Spanske vokativer set i et pragmatisk-funktionelt perspektiv - Andersen, Vibeke (HERMES - Journal of Language and Communication in Business, 2001)
Vocatives have never played a central role in linguistic research in either the field of grammar or in pragmatics. The aim of the present article is to focus on the pragmatic functions of Spanish vocatives in the context of speech acts. During my investigations for my PhD project on deictic expressions it became clear that vocatives are used for many purposes in Spanish dialogue. I also noticed that the use of vocatives was in many cases related to the concept of „face“. In the following I discuss eight different pragmatic functions of vocatives, including their role as down and upgraders in face-threatning and face-supporting acts.